Implementation of Road Infrastructure Development Program in East Lombok Regency (Study at the East Lombok Regency Pupr Service) - Moh, Lalu; Fajri, Nazar (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
This research is entitled Implementation of the Road Infrastructure Development Program in East Lombok Regency. The aim of this research is to find out the extent of the implementation of the Public Works and Spatial Planning Service program in Road Infrastructure Development in East Lombok Regency. The research method used is descriptive qualitative with data collection techniques through observation, interviews, documentation and triangulation. Informants in this research included various related parties, ranging from officials from the Public Works and Spatial Planning Department to the general public. The data obtained was analyzed through data reduction techniques, data presentation, and drawing conclusions. The research results show that the implementation of the road infrastructure development program in East Lombok Regency by the Public Works and Spatial Planning Service has not gone well. Communication is still lacking, as can be seen from the lack of response to community proposals, resources, especially in terms of budget and human resources, are still an obstacle, even though the disposition of the Department is considered good. The bureaucratic structure is also considered not optimal because there are still damaged and potholed roads.